Pengembangan Pendidikan Kesehatan Tentang Pengenalan Sumber Penyakit Dan Penanganannya Kepada Masyarakat Menggunakan Website dengan metode Agile - Muhammad Fauzi; Muhamad Ihsan Hasanudin; Muhammad Sadam Ramadhoni; Ricardus Mba Dala Pati (Politeknik Kampar, 2024)
This study aims to develop health education regarding disease identification and management for the community using a website. The development process incorporates the principles of health promotion and utilizes online platforms to disseminate information effectively. Through this initiative, the community gains access to comprehensive resources on disease identification, preventive measures, and appropriate management strategies. The website serves as a user-friendly tool to enhance health literacy and empower individuals to make informed decisions about their well-being.